Avaliação da emergência de intraverbais em crianças com transtorno do espectro do autismo, após o ensino de tato e de discriminações condicionais - Caixeta, Luiza Magalhães (2019)
Verbal behavior, conceived as operant behavior, can be classified according to its functions. Among verbal operants, two types, tact and intraverbal, are essential in the development and enhancement of communication skills. Among verbal operants, two types, tact and intraverbal, are essential in the development and enhancement of communication skills, so systematically assessing the effect of tact (item and category) teaching and listener relationship teaching. (of items and categories), in the emergence of intraverbal responses becomes relevant both to advance knowledge about the learning processes of these repertoires, and to plan interventions with the purpose of increasing and improving the verbal behavior of individuals diagnosed with ASD. The aim of this research was to evaluate the effects of teaching some conditional discriminations (listener repertoire) and tact (speaker repertoire) on the emergence of intraverbal responses in children diagnosed with ASD. Relations between nonverbal stimuli and the names of pictures and between nonverbal stimuli and the names of categories were taught by two procedures: pairing with the auditory-visual matching-to-sample (MTS) model (listener) and transferring vocal response modeling under simultaneous control of stimulus composed by the nonverbal stimulus (the picture) and its spoken name (speaker). Emergence probes of intraverbal response (controlled by questions which had the names of the item or the category as answers) were conducted before, throughout and at the end of the teaching phases. The connections directly taught were learned by all four participants, but no participant demonstrated the emergence of intraverbals, neither after the tact teaching nor after the MTS teaching, nor after both. However, direct teaching of intraverbal for pictures and categories was successful with three of the participants and may have been benefited from prior learning that included the same response components, but with different functions. Successive probes played an important role in monitoring target behaviors.